Pengaruh Kepemimpinan Visioner Kepala Sekolah, Lingkungan Kerja Sekolah, Komitmen Afektif Guru terhadap Kinerja Inovatif Guru MIS se-Kecamatan Rantau Utara Kabupaten Labuhanbatu - Mardiah Hayati; Salim Aktar; Muhammad Isman (EDUTECH, 2023)
This study aims to determine the effect of: (1) the principal's visionary leadership on the innovative performance of teachers; (2) the school work environment on the innovative performance of teachers; (3) the teacher's affective commitment to the innovative performance of the teacher and (4) the principal's visionary leadership, school work environment and teachers' affective commitment together to the innovative performance of teachers. The research population was MIS teachers in Rantau Utara District with a total sample of 53 peoples. The research method is a correlational quantitative research method with three independent variables and one dependent variable. Based on hypothesis testing, it can be concluded that there is a significant effect between: (1) the principal's visionary leadership on the innovative performance of teachers by 0.527; (2) the school work environment on the innovative performance of teachers is 0.392; (3) the affective commitment of teachers to the innovative performance of teachers is 0.399 and (4) the principal's visionary leadership, school work environment, and teachers' affective commitment together to the innovative performance of teachers are 0.659. Overall, the results of the study indicate that the improvement of teachers' innovative performance is influenced by the visionary leadership of the principal, the school work environment and the affective commitment of teachers by 43.4%; while the remaining 56.6% is determined by other factors